The Node Arrangement Methodology of Wireless Sensor Networks for Long-Span Bridge Health Monitoring. (5th October 2013) - Zhou, Guang-Dong; Yi, Ting-Hua
Abstract : Wireless sensor networks (WSNs), which are a promising technology for the implementation of long-span bridge health monitoring, have gained increasing attention from both the research community and actual users. The limited energy of sensor emphasizes the importance of performance optimization of WSNs. In this paper, a methodology and strategy of node arrangement are developed to improve the performance of WSN for long-span bridge health monitoring, including balancing energy consumption, increasing data capacity, and reducing deployment cost. A composite WSN organized by sensor nodes and relay nodes is introduced for structural health monitoring. The energy consumption model of the composite WSN is firstly presented. And then, the data acquisition efficiency (DAE) defined as data capacity per unit deployment cost is suggested to evaluate the performance of WSN. Subsequently, the node arrangement is divided into two phases of sensor node arrangement and relay node arrangement. An improved general genetic algorithm is proposed to configure sensor nodes, and a nonuniform node arrangement method is developed to distribute relay nodes. Based on the DAE, the theoretical formulae of nonuniform node arrangement are deduced. The process of two-phase node arrangement is also provided for practical bridge engineers.